140. Symptoms and Situations Predispose Patients to Use Antibiotics Without Medical Advice. (31st December 2020) - Hansen, Michael; Trautner, Barbara; Zoorob, Roger; Germanos, George; Alquicira, Osvaldo; Salinas, juanita; Barning, Kenneth; Mahmood, Hammad; Gonzalez, Malissa A; Fowler, Michele; Grigoryan, Larissa
Abstract: Background: Use of antibiotics without a prescription (non-prescription use) contributes to antimicrobial resistance. Non-prescription use includes obtaining and taking antibiotics without a prescription, taking another person's antibiotics, or taking one's own stored antibiotics. We conducted a quantitative survey focusing on the factors that impact patients' decisions to use non-prescription antibiotics. Methods: We surveyed patients visiting public safety net primary care clinics and private emergency departments in a racially/ethnically diverse urban area. Surveys were read aloud to patients in Spanish and English. Survey domains included patients' perspectives on which syndromes require antibiotic treatment, their perceptions of health care, and their access to antibiotics without a prescription. Results: We interviewed 190 patients, 122 from emergency departments (64%), and 68 from primary care clinics (36%). Overall, 44% reported non-prescription antibiotic use within the past 12 months. Non-prescription use was higher among primary care clinic patients (63%) than the emergency department patients (39%, p = 0.002). The majority felt that antibiotics would be needed for bronchitis (78%) while few felt antibiotics would be needed for diarrhea (30%) (Figure 1). The most common situation identified "in which respondents would consider taking antibiotics without contacting a healthcare provider was "got better by taking this antibiotic before" (Figure 2). Primary care patients were more likely to obtain antibiotics without prescription from another country than emergency department patients (27% vs. 13%, P=0.03). Also, primary care patients were more likely to report obstacles to seeking a doctor's care, such as the inability to take time off from work or transportation difficulties, but these comparisons were not statistically significant. Figure 1. Patients' agreement that antibiotics would be needed varied by symptom/syndrome. Figure 2. Situations that lead to non-prescription antibiotic use impacted the two clinical populations differently Conclusion: Non-prescription antibiotic use is a widespread problem in the two very different healthcare systems we included in this study, although factors underlying this practice differ by patient population. Better understanding of the factors driving non-prescription antibiotic use is essential to designing patient-focused interventions to decrease this unsafe practice. Disclosures: All Authors : No reported disclosures